The Importance of the Opinion of Police Officers as Professional Public for the Formulation of Strategies in the Field of Security - Sotlar, Andrej; Tominc, Bernarda (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
Strategic documents are essential to determine (security) activities and ways to achieve them. In the process of assessing the current situation and in the process of establishing action plans, a range of factors and stakeholders must be considered. To achieve an integrated approach to security provision, strategic guidelines should be grounded on thoughtful analysis. It is necessary to consider not only the lay public’s opinion but also a specific part of the professional public – police officers. Police officers build their opinions on direct experiences. This contributes to a better understanding of security threats and internal security issues in general. We assumed that opinions of police officers could play a significant role in shaping security strategies, especially at the local level, as police officers who live/or work there best understand the needs of (local) community. The actual scope of the opinion of this professional public was not determined in this paper.